Building surveyor in property maintenance management / Wan Mohammad Fathi Wan Nawang - Wan Nawang, Wan Mohammad Fathi; Said, Al-Malik Saifulnizam; Azmi, Muhammad Redzuan; Jail, Mohd Khairil (2002)
The quality of the personality and character needed for managerial position are no longer themselves for conduct of the business. In the presenty highly competitive world, they need to be supplemented by extensive specialist knowledge.